Grading as a Type of Assessment: between statistical analysis and learners motivation - Valdevit, Mirna (Array, 2008)
This paper discusses grading in educational system, esp. in Croatian language courses. The first part of the paper shows how grades in Croatian schools and universities cover two types of assessment: ordinal and numeric. The first shows only the rank within a particular class or with respect to criteria of a particular teacher. The second shows numerical relationship and could be viewed as more objective. An example will be presented to show the advantages and disadvantages of grades as the final assessment expresses by only one number. The special emphasis will be put on the assessment of Croatian as L2. As the assessment should play an important role in informing the students plurilingual of their progress, the grading based on arithmetic assessment will be proposed if the grade has to be expressed numerically.